2019
DOI: 10.3390/nu11112765
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Early Initiation of Breastfeeding in Economic Community of West African States (ECOWAS)

Abstract: The early initiation of breastfeeding (EIBF) within one hour after birth enhanced mother–newborn bonding and protection against infectious diseases. This paper aimed to examine factors associated with EIBF in 13 Economic Community of West African States (ECOWAS). A weighted sample of 76,934 children aged 0–23 months from the recent Demographic and Health Survey dataset in the ECOWAS for the period 2010 to 2018 was pooled. Survey logistic regression analyses, adjusting for country-specific cluster and populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
58
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 39 publications
9
58
2
Order By: Relevance
“…In terms of size at birth, babies born with average and large sizes are more likely to be initiated into early breastfeeding than babies with small sizes at birth. This finding is similar to those from studies in Nepal [38] and West Africa [37]. Mothers and healthcare providers perceive that large size infants are healthy and they are associated with physical maturity, proper functions of suckling and deglutination [37,38].…”
Section: Plos Onesupporting
confidence: 86%
See 2 more Smart Citations
“…In terms of size at birth, babies born with average and large sizes are more likely to be initiated into early breastfeeding than babies with small sizes at birth. This finding is similar to those from studies in Nepal [38] and West Africa [37]. Mothers and healthcare providers perceive that large size infants are healthy and they are associated with physical maturity, proper functions of suckling and deglutination [37,38].…”
Section: Plos Onesupporting
confidence: 86%
“…This finding is similar to those from studies in Nepal [38] and West Africa [37]. Mothers and healthcare providers perceive that large size infants are healthy and they are associated with physical maturity, proper functions of suckling and deglutination [37,38]. Therefore, average or large sizes at birth may facilitate EIBF.…”
Section: Plos Onesupporting
confidence: 85%
See 1 more Smart Citation
“…Detailed information on the survey methodology is provided in the final NDHS reports [24][25][26][27][28]. In the present study, a total weighted sample of 103,903 most recent live-birth children under 5 years of age was used to minimize the potential effect of recall bias, consistent with Measure DHS approach [24] and used in previously published studies [29][30][31][32].…”
Section: Data Sourcesmentioning
confidence: 99%
“…Reports showed that residence (15,16), place of delivery (15), Postnatal care (17), maternal educational status (16)(17)(18)(19), maternal age (17), wealth index (18,20), age of the infants (18), gender and birth order of the infant (18,20), delivery mode (16,19) were significantly associated with early initiation of breastfeeding.…”
mentioning
confidence: 99%